Slovakia the ground we stand on - Struhar, Laco, 1954-; Struhar, Laco, 1954-; Bellan, Stano, 1962- (Spektrum Grafik, 2000)
A set of two books with photographs by Lac Struhár and English texts by Stan Bellan. The first book, entitled Garden of Dreams, contains photographs of beautiful natural scenery, which are complemented by poetic texts. The second book, entitled Earth Under the Feet, is divided into eight parts, just as the Slovak Republic is divided into eight regions, which are arranged in alphabetical order. The book contains photographs of the most beautiful cultural monuments and natural beauties of individual territorial units, supplemented by poetic texts by Stan Bellan. English text